2017
DOI: 10.1016/j.gca.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of diagenetic recrystallization on the Mg isotopic composition of marine carbonates

Abstract: The Mg and Sr isotopic compositions (δ 26 Mg and 87 Sr/ 86 Sr) of pore fluids and bulk carbonates from Ocean Drilling Project Site 1171 (South Tasman Rise; 2148.2 m water depth) are reported, in order to evaluate the potential of diagenesis to alter carbonate-based geochemical proxies in an open marine system. Given the trace amounts of Mg in marine carbonates relative to coexisting pore fluids, diagenesis can alter carbonate δ 26 Mg, a promising proxy for seawater δ 26 Mg that may help elucidate long-term cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 96 publications
1
7
0
Order By: Relevance
“…2b). These findings are consistent with studies of net fractionation of magnesium isotopes during diagenesis 24,34 . A simple binned regression of sites (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…2b). These findings are consistent with studies of net fractionation of magnesium isotopes during diagenesis 24,34 . A simple binned regression of sites (Fig.…”
Section: Resultssupporting
confidence: 91%
“…All measured magnesium isotope analytical data are provided in the Supplementary Table 4. Additional pore water magnesium isotope values from ODP Sites 925, 984, 1012, 1082, 1086, 1171, and 1219, and IODP Sites U1378 and U1395 were obtained from published sources 24,34,63 . Other sites with available pore water magnesium isotope data are excluded that are either sparse near the sediment-water interface, affected by brine diffusion, or associated with unquantified pore water advection in the upper sediment section, including ODP Sites 807, 1003, 1052, 1196, 1265, and IODP Site U1403 17,63,64 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jonas et al (2017) demonstrated that, at elevated temperatures, rockbuffered alteration is generally diffusion-driven, with the host-rock dominating the petrographic and geochemical signature of the secondary phase. Many systems have shown to vary in their behavior between given proxies, with more fluid-buffered behavior for one (i.e., O) and more rock-buffered for another (i.e., C, Ca, or Mg; Pingitore, 1982;Geske et al, 2012;Chanda and Fantle, 2017), adding further complexity to the discussion. We suggest that internal fluids and organics can have a large effect on the diagenetic progression of carbonate archives, and play a much larger role in more internally rock-buffered systems, with increasing solid-to-fluid ratios at a local level.…”
Section: Textures: Rock-buffered Versus Fluid-buffered Systems and The Role Of Internal Organicsmentioning
confidence: 99%
“…Before reconstructing secular trends in silicate weathering using any proxy archive, be it siliciclastic or carbonate, it is crucial to consider the effect of post-depositional (or postformational) alteration of the archive (i.e., diagenesis). Bulk carbonates have been shown to react and recrystallize relatively rapidly (Fantle and DePaolo, 2007;Fantle, 2015;Gorski and Fantle, 2017;Huber et al, 2017), impacting strontium, oxygen, and magnesium isotope compositions and Mg/Ca ratios (Richter and DePaolo, 1987;Schrag et al, 1992;Fantle and DePaolo, 2006;Chanda and Fantle, 2017). In contrast to elements such as Ca and Sr, and similar to Mg, Li has a low concentration in carbonates (1-2 ppm;Hoefs and Sywall, 1997;Burton and Vigier, 2012) compared to its concentration in siliciclastics (50-500 ppm; Hein et al, 1979;Zhang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%